2017
DOI: 10.4172/2167-0889.1000205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Aflatoxin M1 in Livestock Livers from Minna, Nigeria

Abstract: Liver as an organ of metabolism is disposed to toxins deposition and Livestock liver contributes to food security as major source of protein. Aflatoxin M1 (AFM1) is a carcinogenous metabolite aflatoxin B1 resulting from hydroxylation. To elucidate aflatoxin M1 incidence and levels in livestock livers from Minna-Nigeria, 24 hours fresh liver samples (n=122; 72 cow livers and 50 goat livers) were collected from five abattoirs and subjected to standard aflatoxin extractions via column chromatography and quantific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Makun et al [67] also reported contamination of raw cow milk with AFM 1 at levels higher than the EU permitted levels in Nigeria. In their study, contamination of raw cow milk (from nomadic cows) with AFM 1 ranged from 0.0109 to 1.3543 µg/L (10.9–1354.3 ng/L) with and an average concentration of 0.5308 ± 0.0938 µg/L (530.8 ng/L).…”
Section: Discussionmentioning
confidence: 97%
“…Makun et al [67] also reported contamination of raw cow milk with AFM 1 at levels higher than the EU permitted levels in Nigeria. In their study, contamination of raw cow milk (from nomadic cows) with AFM 1 ranged from 0.0109 to 1.3543 µg/L (10.9–1354.3 ng/L) with and an average concentration of 0.5308 ± 0.0938 µg/L (530.8 ng/L).…”
Section: Discussionmentioning
confidence: 97%
“…Makun et al 50 also reported contamination of raw cow milk with AFM 1 at levels higher than the EU permitted levels in Nigeria. In their study, contamination of raw cow milk (from a nomadic cow) with AFM 1 ranged from 0.0109 to 1.3543 µg/L (10.9–1354.3 ng/L) with and an average concentration of 0.5308 ± 0.0938 µg/L (530.8 ng/L).…”
Section: Discussionmentioning
confidence: 97%